2018
DOI: 10.1039/c8ta02102c
|View full text |Cite
|
Sign up to set email alerts
|

A facile access to stiff epoxy vitrimers with excellent mechanical properties via siloxane equilibration

Abstract: Recycling process of epoxy vitrimers based on siloxane equilibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 39 publications
0
125
0
Order By: Relevance
“…Using SiO 2 nanoparticles as cross-linkers, recently trials have been made (with the thus created interfacial silyl ether linkages) for epoxy polymers (as vitrimers) towards improving selfhealing and mechanical performances. [230] Legrand et al [231] demonstrated the effect of SiO 2 surface chemistry on the relaxation dynamics in epoxy vitrimer PNCs (Figure 28). The authors found that functionalization of SiO 2 aided in covalent cross-links in the vitrimer matrix via exchangeable bonds and occurred both in the bulk network and at the epoxy-SiO 2 interface.…”
Section: Vitrimers In Self-healing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using SiO 2 nanoparticles as cross-linkers, recently trials have been made (with the thus created interfacial silyl ether linkages) for epoxy polymers (as vitrimers) towards improving selfhealing and mechanical performances. [230] Legrand et al [231] demonstrated the effect of SiO 2 surface chemistry on the relaxation dynamics in epoxy vitrimer PNCs (Figure 28). The authors found that functionalization of SiO 2 aided in covalent cross-links in the vitrimer matrix via exchangeable bonds and occurred both in the bulk network and at the epoxy-SiO 2 interface.…”
Section: Vitrimers In Self-healing Materialsmentioning
confidence: 99%
“…Vitrimers follow the Arrhenius law in exhibiting the gradual thermal viscosity behavior, that endowed the composites with glass-like malleability and reprocessability without any precise temperature control. [222][223] To date, a variety of exchangeable chemical reactions [223][224][225][226][227][228][229][230] (transesterification, transalkylation, transamination, olefin metathesis, boroxine metathesis, disulfide, imine and siloxane-silanol exchange) have been explored in the context of vitrimers, to improve and expand both the performance and gallery of vitrimer materials. Using SiO 2 nanoparticles as cross-linkers, recently trials have been made (with the thus created interfacial silyl ether linkages) for epoxy polymers (as vitrimers) towards improving selfhealing and mechanical performances.…”
Section: Vitrimers In Self-healing Materialsmentioning
confidence: 99%
“…Indeed, this silicone rubber material showed self‐healing properties after being heated at 90 °C for 24 h (Figure B). Since the report of Zheng and McCarthy, several groups further explored this chemistry in various dynamic materials . Recently, Seiffert et al.…”
Section: Si−o Exchange In Siloxanes and Silyl Ethersmentioning
confidence: 99%
“…In the above sections, various representative vitrimerization methodologies for industrial polymers were described. Of course, the vitrimerization of other non-classifiable polymers with unique functions, e.g., strong hydrophobicity or hydrophilicity, have been reported by several groups [71][72][73]. In addition to the abovementioned examples, there are recent trends in the vitrimer molecular designs.…”
Section: Other Trends For the Practical Application Of The Vitrimer Cmentioning
confidence: 99%